Trace Element Analysis of Black Foods by ICP-AES - Yan, Qinghua; Yang, Li; Niu, Liyuan; Feng, Huigen (Asian Journal of Chemistry, 2011)
A method for determination nineteen trace elements of Se, Zn, Ni, B, Mn, Fe, Mg, Be, Ca, Cu, Ba, Na, K, P, As, Pb, Cd, Cr and Al in five black foods (black bean, black rice, black sesame, black tree fungus and seaweed) by inductively coupled plasma atomic emission spectrometry has been suggested and sufficient experimental conditions of microwave digestion have been studied. The accuracy of the method was validated using the Chinese reference material GBW08517 Sesame and GBW08502 rice. The multi-element standard solutions (5 mg/kg) as a correction technique was explored. Results showed concentrations of all elements displayed a wide variability among those black foods, except for Se, Pb, Cr, Be and Ba. The predominant element was K, followed by P, Ca, Mg and Na. The medium content was Al, Fe, B, Zn, Mn and Cu. Meanwhile, high levels of As, Pb and Cr were found in seaweed. Therefore, it is important to have a good quality control for black foods in order to protect consumers from health risks for consumption.